Apical and basolateral plasma membranes in epithelial cells have distinct lipidomes and biophysical properties - Carolyn R. Shurer; Kandice R. Levental; Ilya Levental (Proceedings of the National Academy of Sciences, 2026)
Epithelial cell polarization is essential for many physiological processes, including tissue morphogenesis, nutrient absorption, barrier integrity, and directional secretion. A defining feature of such polarization is the separation of plasma membrane (PM) lipids and proteins into distinct apical and basolateral compartments. It has long been suggested that the apical compartment is rich in glycolipids and cholesterol and that this composition arises through trafficking of self-assembled membrane domains (termed lipid rafts). However, neither the detailed composition nor the mechanisms of molecular sorting between epithelial cell PM compartments have been fully resolved. Particularly, the lipid profile of the basolateral membrane and consequently the lipid disparity between the apical and basolateral membrane remain undefined. We developed a method to separately isolate the apical and basolateral PM and used lipidomics and biophysical profiling to characterize the changes in membrane composition and properties between these compartments in polarized Madin–Darby canine kidney cells. We find that the apical membrane is enriched in cholesterol, saturated lipids, and glycolipids relative to the basolateral membrane and that its biophysical properties reflect a more ordered environment. Further, we evaluate the longstanding hypothesis that lipid rafts contribute to apical protein trafficking by assessing the relationship between transmembrane domain raft affinity and apical localization and find that lipid raft affinity only modestly influences apical versus basolateral sorting. These findings define the distinct compositional and biophysical features of apical and basolateral compartments of epithelial cells and suggest mechanistic evidence for their biogenesis.